PERBANDINGAN JADWAL DAN BIAYA PROYEK DENGAN LINEAR SCHEDULING METHOD (LSM) - Tania Asyura Shafa Hamidah, - (2022)
Project scheduling is one of the stages in a construction project which one of its functions is to be a control tool in the implementation stage to avoid delays. On the planning stage, it is necessary to develop an appropriate scheduling method according to the characteristics of the project so that the controlling activities carried out are easier and in accordance with the implementation method. Project scheduling that applied in Indonesia is generally still uses the barchart method. The FKPD Government Building Construction Projects can be categorized into a building projects that have repeated activities, so it is a repetitive project. For projects that are repetitive, scheduling with the Linear Scheduling Method (LSM) can be applied. The scheduling with LSM greatly influences toward the changes in time and costs that are carried out by taking into account the duration of the project and depicted on the LSM diagram to show conflicts in each work, so this method can minimize problems that occur in the field. The results of the calculation analysis using the Linear Scheduling Method (LSM) show that there is a change in project age and work costs per week. The duration of the project life is 6,25% faster, which is 8 days faster compared to the barchart scheduling from 48 days to 45 days and there are also changes in work costs every week.